N-(4-Chlorophenyl)-2,4-dimethylbenzenesulfonamide - K. Shakuntala; Sabine Foro; B. Thimme Gowda (Acta Crystallographica Section E, 2011)
Molecules of the title compound, C14H14ClNO2S, are bent at the S atom with a C—SO2—NH—C torsion angle of 57.7 (2)°. The benzene rings are rotated relative to each other by 68.1 (1)°. In the crystal, N—H...O(S) hydrogen bonds pack the molecules into infinite chains parallel to the b axis.